Utilizing analytics within the realm of e-commerce to manage the procurement - Hnatchuk, Alina (2024)
The thesis focuses on examining the utilizing of data analytics in e-commerce specifically for product supply management. The initial section of the qualification work explores the capabilities and methods of data analytics, discussing its applications across various fields and emphasizing its relevance in e-commerce. The second section delves into the supply chain, analysing its management through analytics and investigating tools for data analytics in e-commerce. The third section provides a synthesis of the findings regarding the influence of data analytics on e-commerce. It includes an analysis of the application of Google Analytics and Noibu. The object of study is an e-commerce project, with the research centring on the impact of data analytics from both the supplier and end-user perspectives.